Evaluasi Kepuasan Pengguna Layanan Administrasi Satu Pintu di Perpustakaan Universitas Andalas Menggunakan Metode Servqual - Andi Saputra (Media Pustakawan, 2024)
One-stop administration services are one of the approaches designed to provide ease of access and integrated concepts to the various services offered. This study aims to evaluate the implementation of one-stop administrative services in the front office of the Unand Library by collecting the perception and satisfaction of service users using the Servqual method. This research is quantitative. The study's results were processed using a descriptive statistical method by examining the influence of respondents' demographics, such as gender, year of entry, and study level, on user satisfaction. The study's overall results show that the level of user satisfaction with one-stop administrative services at the Unand Library is very high. The hypothesis test indicates that the year of entry significantly affects user satisfaction. The average satisfaction of old students tends to be higher than new students. Meanwhile, gender and study level did not significantly affect user satisfaction. The high level of user satisfaction is one of the reasons for the considerable disparity between the current and previous service quality. In addition, users also highlighted the lack of service staff and internet network disruptions in the front office. Overall, it can be concluded that one-stop administration services contribute positively to improving the efficiency and effectiveness of services in libraries, and service innovation is indispensable in libraries to increase user satisfaction.